2001
DOI: 10.1021/ja0030919
|View full text |Cite
|
Sign up to set email alerts
|

Endo−Exo and Facial Stereoselectivity in the Diels−Alder Reactions of 3-Substituted Cyclopropenes with Butadiene

Abstract: A computational examination of the four modes of addition in the Diels-Alder reactions of 3-substituted cyclopropene derivatives (substituents: BH(2), CH(3), SiH(3), NH(2), PH(2), OH, SH, F, and Cl) with butadiene have been carried out at the B3LYP/6-31++G(d)//HF/6-31++G(d) level. The degree of stabilization of these derivatives at the ground state correlates with the electronegativity of the substituent. This attenuation of reactivity and differences in steric interactions are the only factors needed to expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…9 (c) Poirier and Burnell have investigated the reactions of cyclopropene and 3-BH2/CH3/SiH3/NH2/PH2/OH/SH/F/Cl substituted cyclopropenes with butadiene at the B3LYP/6-31++G(d)//HF/6-31++G(d) level and concluded that there was no contribution of the SOI to the stereoselectivity. 10 (d) Gosse and Poirier have studied the reaction of butadiene with 3,3-disubstituted cyclopropenes (the substituents were CH3, SiH3, NH2, PH2, OH, SH, F and Cl) at the B3LYP/6-31++G(d) level and observed that the exo TS structure was consistently favored over the corresponding endo TS structure. 11 (e) Lewandowski and Houk have very recently studied the reactions of cyclopropene, 3-substituted cyclopropenes and 3,3-disubstituted cyclopropenes with butadiene at the M06-2X/6-31+G(d) density functional level and suggested that factors such as hyperconjugation, electrostatic and steric effects also contributed along with the SOI to the stereoselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…9 (c) Poirier and Burnell have investigated the reactions of cyclopropene and 3-BH2/CH3/SiH3/NH2/PH2/OH/SH/F/Cl substituted cyclopropenes with butadiene at the B3LYP/6-31++G(d)//HF/6-31++G(d) level and concluded that there was no contribution of the SOI to the stereoselectivity. 10 (d) Gosse and Poirier have studied the reaction of butadiene with 3,3-disubstituted cyclopropenes (the substituents were CH3, SiH3, NH2, PH2, OH, SH, F and Cl) at the B3LYP/6-31++G(d) level and observed that the exo TS structure was consistently favored over the corresponding endo TS structure. 11 (e) Lewandowski and Houk have very recently studied the reactions of cyclopropene, 3-substituted cyclopropenes and 3,3-disubstituted cyclopropenes with butadiene at the M06-2X/6-31+G(d) density functional level and suggested that factors such as hyperconjugation, electrostatic and steric effects also contributed along with the SOI to the stereoselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the huge amount of effort devoted to the analysis of archetypal reactions, in comparison, the number of theoretical works dealing with the effect of (aliphatic) substituents on the reactivity‐selectivity of Diels‐Alder cycloadditions is scarce . The most recent studies are focused on the reaction of substituted cyclopropenes with butadiene, showing the relevance electrostatic interactions as well as SOI and charge transfer interactions…”
Section: Introductionmentioning
confidence: 99%
“…The authors proposed the existence of attractive secondary orbital interactions (SOI) between p orbitals not directly involved in the formation of the new sigma bonds as underlying reason for such selectivity. Although SOI has been invoked to explain preference of endo's cycloadduct formation, [4] even in textbooks, its existence has been criticized over the years [5] and the debate is still open.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the same simulation, the results for gem-difluorocyclopropene adduct 8 reveal a heat of formation of -0.588 and 0.65Kcal/mole with activation energies of 23.66 and 25.26 Kcal/mol for exoand endo-isomer respectively, while the distance between the oxygen atom and the fluorine atom range from 2.500 to 2.672Å and 2.537 to 2.703 Å for exo-and endo-adduct, respectively, which are very close to van der Waal's radii (2.75Å). 15 The low heat of formation of adduct 8 indicates its instability that is responsible for slowing down the cycloaddition between gemdifluorocyclopropene and furan.…”
mentioning
confidence: 99%